PARTISIPASI ANGGOTA KELOMPOK TANI TERNAK LEMBU KARYA PADA UNIT KEGIATAN PENGOLAHAN PUPUK ORGANIK DI DUSUN BLENDENGAN DESA TEGALTIRTO KECAMATAN BERBAH KABUPATEN SLEMAN - Gigih Ambarwati; Daru Retnowati; Agus Santosa (Jurnal Dinamika Sosial Ekonomi, 2018)
This study aims to determine the participation rate of members of the Livestock Farmer Group Lembu Karya and to know the factors that influence the participation rate of members of the Livestock Farmer Group Lembu Karya in the processing of organic fertilizers. The method used in this research is care study method. The data used in this research are primary data and secondary data. Technique of collecting data by interview and recording. To measure the participation rate of members of the Livestock Farmer Group Lembu Karya using Likert scale, while the results of the partipation level study included in the high category. To measure the analytical technique to know the factors that influence the participation rate of Livestock Farmer Group Lembu Karya with multiple linear regression, while the result of research that influence the factors are age, income level and job while the factors that do not affect the income and the length of stay. Keywords: Participation, Organic Fertilizer, Livestock Farmer Group Lembu Karya